Marginal public health gain of screening for colorectal cancer: modelling study, based on WHO and national databases in the Nordic countries. Issue 2 (22nd April 2012) - Sigurdsson, Johann A.; Getz, Linn; Sjönell, Göran; Vainiomäki, Paula; Brodersen, John
Abstract: Aims To estimate the potential gain of national screening programmes for colorectal cancer (CRC) by stool occult blood testing in the Nordic countries, with comparative reference to the burden of other causes of premature death. Methods Implementation of national screening programmes for CRC was modelled among people 55–74 years in accordance with the 2011 Cochrane review of biannual screening, using the faecal occult blood test (FOBT) for 10 years, resulting in 15% relative risk reduction in CRC deaths among all those invited [intention‐to‐treat; relative risk 0.85; confidence interval (CI) 0.78 to 0.92]. Our calculations are based on the World Health Organization and national databanks on death causes (ICD‐10) and the mid‐year number of inhabitants in the target group. For Finland, Denmark, Norway and Sweden, we used data for 2009. For Iceland, due to the population's small size, we calculated mean mortality for the period 2005–2009. Results Invitation to a CRC screening programme for 10 years could influence 0.5–0.9% (95%CI 0.4–1.2) of all deaths in the age group 65–74 years. Among the remaining 99% of premature deaths, around 50% were caused by lung cancer, other lung diseases, cardiovascular diseases and accidents, with some national variations. Conclusions and implications Establishment of a screening programme for CRC for people aged 55–74 can be expected to affect only a minor proportion of all premature deaths in the Nordic setting. From a public health perspective, prioritizing preventive strategies targeting more prevalent causes of premature death may be a superior approach.